Multiple origins of the i heterokaryon gene in Rockefeller-Lindegren strains - J F Wilson; M L Holden (Fungal Genetics Reports, 2001)
The Fungal Genetics Stock Center has been able to revive four old lyophilized cultures of the mutants used by Garnjobst in her pioneering 1953 study of vegetative incompatibility in Neurospora crassa. One of them, inositolless (37401), tests as het-c,* het-d, het-E, as described by Garnjobst. This strain cannot be tested completely for het-I/i, but it is not het-I/i compatible with the FGSC riboflavinless het-cdE I tester strain. The other early cultures were the standard Rockefeller-Lindegren het-CDEI. A lineage chart of the het-e strains in the Wilson-Garnjobst heterokaryon testers shows that many of the inl testers are het-i, which probably accounts for the erratic performance observed in growth tubes with these testers. A list of het-I/i genotypes of 31 FGSC strains is included.